Evaluation of imazapic and flumioxazin carryover risk for Carinata (Brassica carinata) establishment - Camacho Umaña, Manuel Ernesto (2022)
Carinata (Brassica carinata A. Braun) is a potential crop for biofuel production, but the risk of injury resulting from carryover of soil herbicides used in rotational crops is of concern. The present study evaluated the carryover risk of imazapic and flumioxazin for carinata. Label rates of imazapic (70 g ai ha−1) and flumioxazin (107 g ai ha−1) were applied 24, 18, 12, 6, and 3 mo before carinata planting (MBP). The same herbicides were applied preemergence right after carinata planting at 1X, 0.5X, 0.25X, 0.125X, 0.063X, and 0X the label rate. When either herbicide was applied earlier than 3MBP, there was no difference in plant density compared with the nontreated control. Carinata damage was <25% when flumioxazin or imazapic was applied at least 6 MBP in Clayton, NC (sandy loam soil), while in Jackson Springs, NC (coarser-textured soil and higher precipitation), at least 12 MPB were needed to lower plant damage to <25%. Preemergence application of 0.063X each herbicide decreased plant density by 40%, with damage reaching >25%. Quantification of herbicide residues in both soils showed that imazapicmoved deeper in the soil profile than flumioxazin. Thiswasmore evident in Jackson Springs, where 0.68, 3.52, and 7.77 ng of imazapic g−1 soil were detected (15- to 20-cm depth) when the herbicide was applied at 12, 6 and 3MBP, respectively, while no flumioxazin residues were detected at the same soil depths and times. When residues were 7.78 and 6.90 ng herbicide g−1 soil in the top 10 cm of soil for imazapic and flumioxazin, respectively, carinata exhibited at least 25% damage. Rotational intervals to avoid imazapic and flumioxazin damage to carinata should be between 6 and 12MBP depending on soil type and environmental conditions, with longer intervals for the former than the latter.